2004
DOI: 10.4049/jimmunol.172.4.2569
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun NH2-Terminal Kinase Activity Improves Ischemia/Reperfusion Injury in Rat Lungs

Abstract: Although c-Jun NH2-terminal kinase (JNK) has been implicated in the pathogenesis of transplantation-induced ischemia/reperfusion (I/R) injury in various organs, its significance in lung transplantation has not been conclusively elucidated. We therefore attempted to measure the transitional changes in JNK and AP-1 activities in I/R-injured lungs. Subsequently, we assessed the effects of JNK inhibition by the three agents including SP600125 on the degree of lung injury assessed by means of various biological mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…Many of the commercially available JNK inhibitors are small molecule, ATP competitive inhibitors such as SP600125. This particular inhibitor was found to reduce lung injury caused by ischemia/reperfusion and alleviate damage from smoke inhalation, illustrating the potential of JNK inhibitors as therapeutic drugs (28). Although there has been some success with the ATP competitive inhibitors, some problems have arisen because of their promiscuous nature.…”
Section: Discussionmentioning
confidence: 98%
“…Many of the commercially available JNK inhibitors are small molecule, ATP competitive inhibitors such as SP600125. This particular inhibitor was found to reduce lung injury caused by ischemia/reperfusion and alleviate damage from smoke inhalation, illustrating the potential of JNK inhibitors as therapeutic drugs (28). Although there has been some success with the ATP competitive inhibitors, some problems have arisen because of their promiscuous nature.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the attenuation of hepatic I/R injury by a p38 MAPK inhibitor identifies p38 M APK as a therapeutic target in I/R injury (Kobayashi et al, 2002). JNK has also been suggested as a therapeutic target in reperfusion injury of major organs, such as the brain (Gao et al, 2005) and the lung (Ishii et al, 2004) because it was found that chemical JNK inhibitors attenuate reperfusion injury in these organs. Uehara et al, (2005) recently reported that several novel JNK inhibitors successfully attenuated hepatic I/R injury and increased the survival rate of rats subjected to partial hepatic I/R and resectioning of the remaining non-ischemic lobes.…”
Section: Discussionmentioning
confidence: 99%
“…SP600125, a reversible ATP-competitive inhibitor, selectively inhibits JNK activity (Bennett et al, 2001), reduces ischemia-reperfusion injury in the brain (Gao et al, 2005) and the lungs (Ishii et al, 2004), and protects hepatocytes from apoptosis due to TNF- (Marderstein et al, 2003). Therefore, we attempted to determine whether SP600125 attenuates hepatic I/R injury in vivo using a partial hepatic I/R model in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The MAPK JNK is activated upon exposure to a broad range of stimuli, including osmotic stress (34), heat shock (34), IL-1␤ (35), and TNF-␣ (36), and we have shown recently that JNK is activated in LPS-stimulated neutrophils (37). In addition, a role for JNK in regulating pulmonary inflammation has been suggested recently by our group and others, in that systemic inhibition of JNK decreased acute inflammation after LPS (38), stretch (39), or ischemia-reperfusioninduced lung injury (40). Activation of JNK increases PAI-1 expression in vitro (41,42), and although other mechanisms were proposed for the decrease in acute inflammation with JNK inhibition in the above studies, the role of JNK in mediating PAI-1 expression suggests that JNK activation may increase PAI-1 expression in vivo, and that an increase in PAI-1 levels may be one mechanism regulating pulmonary neutrophil recruitment in models of lung inflammation.…”
Section: P Lasminogen Activator Inhibitor-1 (Pai-1)mentioning
confidence: 95%